The use of solution-oriented coaching to facilitate teacher’s applications of education technology in a primary school - Hunt, Stephanie (2022)
A vision for education redesigned with technology to equip pupils to succeed in the 21st century has been espoused internationally. Technology is reported to enhance learning outcomes, however, applications of technology in schools is varied and complex. This study sought to investigate how solution-oriented coaching could facilitate technology applications, with the aim of promoting teaching and learning.